Novel preoperative computed tomography (CT)-derived parameters to enhance self-expanding metallic stents (SEMS) outcomes in obstructive colorectal cancer - AKÇAY A.; DÖNMEZ Z.; GÜLTEKİN M. A.; PEKER A. A.; Karabulut Ü.; Şahin D.; KİREMİTÇİ S.; ŞENTÜRK H.; Şerefoğlu R.; TOPRAK H. (My University, 2025)
AIM: This study aimed to evaluate whether preoperative computed tomography (CT)-based morphological parameters predict the clinical success of self-expanding metallic stents (SEMS) in malignant colorectal obstruction. MATERIALS AND METHODS: Sixty-six patients with acute malignant colonic obstruction who underwent SEMS placement between 2016 and 2021 were retrospectively analysed. Tumour length, wall thickness, and lumen diameter were measured on preoperative CT, and ratios with SEMS dimensions were calculated. Clinical success was defined as decompression within 96 hours and no further stent-related intervention within three months. RESULTS: A total of 47 patients (71.2%) achieved clinical success, while 19 patients (28.8%) did not. Unsuccessful cases demonstrated significantly greater tumour length (median: 58 mm vs 48 mm, P=.019) and higher tumour thickness-to-lumen diameter ratio (median: 6.66 mm vs 3.9 mm, P=.016). They also exhibited a narrower lumen diameter (median: 2.21 mm vs 2.85 mm, P=.03). Conversely, a higher SEMS length-to-tumour length ratio correlated with successful outcomes (median: 2 mm vs 1.46 mm, P=.009). Factors such as age, tumour wall thickness, colonic angulation, and SEMS diameter-to-lumen diameter ratio were not significantly associated with clinical success (all P>.05). CONCLUSION: Preoperative CT findings—particularly tumour length, lumen diameter, tumour thickness-to-lumen diameter ratio, and SEMS length-to-tumour length ratio—may serve as practical predictors for SEMS success in malignant colorectal obstruction. Incorporating these parameters into patient selection and stent-sizing decisions could improve both immediate and long-term outcomes. Further multicenter, prospective studies are required to validate these findings and optimise SEMS use in clinical practice.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Radyoloji Nükleer Tıp ve Medikal Görüntüleme; Clinical Medicine (Med); Clinical Medicine; Radiology Nuclear Medicine & Medical Imaging; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiology, Nuclear Medicine and Imaging